"Islands of excellence": On the emergence of corporate socials in India. Issue 1 (15th September 2021) - Rigillo, Nicole
Abstract : In 2014, the government of India mandated that India's largest companies devote 2% of their net profits to corporate social responsibility (CSR). Drawing on fieldwork on the CSR activities of Bangalore‐based Titan, a Tata Group company and India's largest watch producer, and Wipro, one of India's largest IT companies, this article contends that government‐mandated biopolitical engagements by Indian corporations forge new iterations of "the social" and are generative of spatially delimited and heterogeneous "corporate socials." Corporate socials can be situated within broader global shifts away from universal forms of social welfare. While these developments may represent the "death of the social, " I contend that they are an emergent modality of government‐mandated service provision by private actors in India, one that is giving rise to a patchwork of plural socials, which proponents argue can also serve as engines of corporate‐led resource redistribution.